Factors Models of Scrum Adoption in the Software Development Process: A Systematic Literature Review - Marilyn Sihuay; Abraham Dávila; Marcelo Pessoa (ReCIBE)
(Background) The adoption of Agile Software Development (ASD), in particular Scrum, has grown significantly since its introduction in 2001. However, in Lima, many ASDs implementations have been not suitable (uncompleted or inconsistent), thus losing benefits obtainable by this approach and the critical success factors in this context are unknown. (Objective) To analyze factors models used in the evaluation of the adoption of ASDs, as these factors models can contribute to explaining the success or failure of these adoptions. (Method) In this study we used a systematic literature review. (Result) Ten models have been identified; their similarities and differences are presented. (Conclusion) Each model identified consider different factors, however some of them are shared by five of these models, such as team member attributes, engaging customer, customer collaboration, experience and work environment.